2016
DOI: 10.1007/s10663-016-9323-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the financial system on economic growth in the context of the global crisis: empirical evidence for the EU and OECD countries

Abstract: This study aims to analyze the impact of the development and stability of the financial sector on economic growth on the basis of the quantitative methods that produce robust results. The following research hypotheses are tested: /H1/ The relationship between financial sector development (stability) and economic growth is nonlinear; /H2/ An excessively large size of the financial system does not lead to more rapid economic growth: it may even negatively affect GDP dynamics; /H3/ The inclusion of the post-crisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 43 publications
3
67
0
4
Order By: Relevance
“…This result in line with economic theory, which indicates that increased funding improves economic growth by augmenting the investment rate. This result is similar to those in transition and developed countries (Cojocaru, Falaris, Hoffman, & Miller, ; Prochniak & Wasiak, ). Indeed, Cojocaru et al () indicated that private credit positively influenced economic growth in the Central and Eastern Europe and the Commonwealth of Independent States countries.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…This result in line with economic theory, which indicates that increased funding improves economic growth by augmenting the investment rate. This result is similar to those in transition and developed countries (Cojocaru, Falaris, Hoffman, & Miller, ; Prochniak & Wasiak, ). Indeed, Cojocaru et al () indicated that private credit positively influenced economic growth in the Central and Eastern Europe and the Commonwealth of Independent States countries.…”
Section: Resultssupporting
confidence: 87%
“…Indeed, Cojocaru et al () indicated that private credit positively influenced economic growth in the Central and Eastern Europe and the Commonwealth of Independent States countries. As for Prochniak and Wasiak () study, it is apparent that the change in domestic credit is a significant factor of economic growth in the European Union countries.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The ratio of domestic credit to private sector to GDP turned out to have a negative impact on the rate of growth of TFP. This means that the "too much finance" hypothesis may be valid for the countries of the Central and Eastern Europe (Próchniak, Wasiak [35]; Grabowski, Maciejczyk-Bujnowicz [15], [16]). …”
Section: We Drop Insignificant Variablesmentioning
confidence: 99%